CRITICISM AS SABOTAGE AND THE STRATEGIES OF DECONSTRUCTION - Arranz Muñoz, Juan (Centro de Investigaciones y Estudios sobre Cultura y Sociedad, 2016)
In his latest book, Crítica y Sabotaje, Manuel Asensi presents a new method of criticism of the artistic discourse — «criticism as sabotage». Helped by a distrustful stance towards the work of art, and by the use of his own terminology, this criticism aims either to uncover (and to sabotage) the way in which the discourses try to impose a certain image of the world to the receiver (thus obtaining from him a certain behavior), or to explain the way in which some particular discourses present themselves as ambiguous and controversial (sabotaging its own affirmative nature, as well as the social system to which they belong).            In this paper, through an attentive reading of Asensi's interpretative proposals, we try to trace the roots that this type of criticism has in the deconstructionist literary theory, with the goal to link Asensi’s work with the ideas and strategies developed by his predecessors Jacques Derrida and Paul de Man. This analysis will, in the end, allow us to identify the deconstruction as the major influence of the critical sabotage, but also to enumerate the discrepancies that separate both criticisms.